1990
DOI: 10.1037/0735-7036.104.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Inferences about guessing and knowing by chimpanzees (Pan troglodytes).

Abstract: The visual perspective-taking ability of 4 chimpanzees (Pan troglodytes) was investigated. The subjects chose between information about the location of hidden food provided by 2 experimenters who randomly alternated between two roles (the guesser and the knower). The knower baited 1 of 4 obscured cups so that the subjects could watch the process but could not see which of the cups contained the reward. The guesser waited outside the room until the food was hidden. Finally, the knower pointed to the correct cup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
246
3
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(258 citation statements)
references
References 33 publications
6
246
3
3
Order By: Relevance
“…Their observations revise earlier findings which suggested that chimpanzees may not be able to recognize the causal link between visual access and knowledge (e.g. Povinelli, Nelson, & Boysen, 1990) and open the way to recognizing some causal reasoning about mental states in non-humans (for discussion, see Povinelli & Vonk, 2003;Tomasello, Call, & Hare, 2003). To the extent that source reasoning can emerge in non-linguistic species, the claim that source reasoning is introduced by linguistic elements becomes much less plausible.…”
Section: Language-on-thought Effects?mentioning
confidence: 52%
“…Their observations revise earlier findings which suggested that chimpanzees may not be able to recognize the causal link between visual access and knowledge (e.g. Povinelli, Nelson, & Boysen, 1990) and open the way to recognizing some causal reasoning about mental states in non-humans (for discussion, see Povinelli & Vonk, 2003;Tomasello, Call, & Hare, 2003). To the extent that source reasoning can emerge in non-linguistic species, the claim that source reasoning is introduced by linguistic elements becomes much less plausible.…”
Section: Language-on-thought Effects?mentioning
confidence: 52%
“…A long-standing tradition held that Btheory of mind^(ToM) is uniquely human (Penn & Povinelli, 2007;Povinelli et al, 1990;Premack & Woodruff, 1978). However, a series of recent experiments with chimpanzees shows that at least a basic capacity to represent the knowledge of others is present in apes (Bräuer, Call, & Tomasello, 2007;Call & Tomasello, 2008;Hare et al, 2000), and very recent data based on eyetracking suggests a capacity to represent false beliefs as well (Krupenye et al, 2016).…”
Section: Semantic and Pragmatic Components Of Languagementioning
confidence: 99%
“…R. Soc. B 370: 20150049 1990s, Povinelli et al [77,78] conducted experiments showing that at least some chimpanzees possessed the ability to attribute certain knowledge to other chimpanzees or humans and to take into account that knowledge in their own behaviour. Later, however, Povinelli and Vonk became sceptical and could find no convincing evidence for the existence of a ToM and knowledge attribution in chimpanzees or other animals, but argued that their own findings could be better explained as the result of operant conditioning [79].…”
Section: (V) Mirror Self-recognitionmentioning
confidence: 99%